Community-Based Screening for Cervical Cancer: A Feasibility Study of Rural Appalachian Women. Issue 11 (November 2015) - Crosby, Richard A.; Hagensee, Michael E.; Vanderpool, Robin; Nelson, Nia; Parrish, Adam; Collins, Tom; Jones, Nebraska
Abstract : Objectives: To describe women's comfort levels and perceptions about their experience self-collecting cervicovaginal swabs for human papillomavirus (HPV) testing, to determine whether nurse-guided patient navigation increases the odds of women receiving a traditional Papanicolaou (Pap) test after HPV screening, and to test the hypothesis that women testing positive for oncogenic HPV would be more likely to have a subsequent Pap test than those testing negative. Methods: A total of 400 women were recruited from 8 rural Appalachian counties, in 2013 and 2014. After completing a survey, women were provided instructions for self-collecting a cervicovaginal swab. Specimens were tested for 13 oncogenic HPV types. Simultaneously, women were notified of their test results and offered initial navigation for Pap testing. Chart-verified Pap testing within the next 6 months served as the end point. Results: Comfort levels with self-collection were high: 89.2% indicated that they would be more likely to self-collect a specimen for testing, on a regular basis, compared with Pap testing. Thirty women (7.5%) had a follow-up Pap test. Women receiving added nurse-guided navigation efforts were significantly less likely to have a subsequent test ( P = 0.01). Women testing positive for oncogenic HPV were no more likely than those testing negative to have a subsequent Pap test ( P = 0.27). Data were analyzed in 2014. Conclusions: Rural Appalachian women are comfortable self-collecting cervicovaginal swabs for HPV testing. Furthermore, efforts to recontact women who have received an oncogenic HPV test result and an initial navigation contact may not be useful. Finally, testing positive for oncogenic HPV may not be a motivational factor for subsequent Pap testing. Abstract : This study of 400 rural women found high ratings of comfort for self-collecting vaginal swabs for human papillomavirus (HPV) testing. Nearly one-third were oncogenic HPV-positive. Papanicolaou testing in the next 6 months was equally low regardless of HPV positivity.